Development of the Referee Shared Mental Models Measure (RSMMM) - Sinval, J.; Aragão e Pina, J.; Sinval, J.; Marôco, J.; Santos, C. M.; Uitdewilligen, S.; Maynard, M.T.; Passos, A. M. (Frontiers in Psychology, 2020)
The concept of shared mental models refers to the shared understanding among team members about how they should behave in different situations. This article aimed to develop a new shared mental model measure, specifically designed for the refereeing context. A cross-sectional study was conducted with three samples: national and regional football referees (n = 133), national football referees and assistant referees and national futsal referees (n = 277), and national futsal referees (n = 60). The proposed version of the Referee Shared Mental Models Measure (RSMMM) has 13 items that are reflected on a single factor structure. The RSMMM presented good validity evidence both based on the internal structure and based on relations to other variables (presenting positive associations with team work engagement, team adaptive performance, and team effectiveness). Such promising psychometric properties point to an optimistic outlook regarding its use to measure shared mental models in futsal and football referee teams.